2015
DOI: 10.1111/1753-6405.12294
|View full text |Cite
|
Sign up to set email alerts
|

The oral health care experiences of NSW Aboriginal Community Controlled Health Services

Abstract: Objectives: Aboriginal people continue to experience a disproportionately heavy burden of oral disease. A range of oral health services may be available to Aboriginal communities, including those provided by Aboriginal Community Controlled Health Services (ACCHSs). This study explored the oral health care experiences and activities of ACCHSs to inform policy and program decision making. Methods: Mixed methods, including an online survey and semi‐structured interviews with senior ACCHS staff, were used. Areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 3 publications
0
46
0
1
Order By: Relevance
“…This was achieved through the use of cultural artefacts [ 51 ], local language [ 62 ] and comfortable surroundings [ 44 ]. Stage Three: Health Care Reaching Patients’ Ability to Reach–eight papers Transport was considered to be the main factor which inhibited Indigenous people from reaching services [ 63 , 64 ] followed by a lack of communication services including telephones [ 65 ]. The lack of transport was further exacerbated when health care services were located outside of peoples’ communities [ 39 , 40 , 45 , 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was achieved through the use of cultural artefacts [ 51 ], local language [ 62 ] and comfortable surroundings [ 44 ]. Stage Three: Health Care Reaching Patients’ Ability to Reach–eight papers Transport was considered to be the main factor which inhibited Indigenous people from reaching services [ 63 , 64 ] followed by a lack of communication services including telephones [ 65 ]. The lack of transport was further exacerbated when health care services were located outside of peoples’ communities [ 39 , 40 , 45 , 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Australia, oral health services are available in public, private and Aboriginal health service contexts. Barriers to good oral health and dental care identified by Aboriginal people include services disrespectful of cultural differences and/or with no Aboriginal Health Workers (AHWs) on staff [ 13 ]; cost, long waiting times, distance to services, especially for those living in remote areas [ 14 ], and limited access to healthy food [ 15 ]. An Aboriginal Health Worker is defined as a person of Aboriginal or Torres Strait Islander descent or who identifies as such and is accepted by the Aboriginal and Torres Strait Islander community; has a minimum qualification in Aboriginal and Torres Strait Islander primary health care and delivers care that is holistic and culturally safe [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Promoting oral health requires improving oral health literacy and involving Aboriginal people in designing strategies to prevent disease that are relevant and context specific [ 13 ]. A recent study of oral health care in Aboriginal Community Controlled Health Services (ACCHS) in New South Wales found that lifting the burden of oral disease in an Aboriginal community leaves more time to promote oral health [ 14 ]. However, even though dental care was sometimes accessible in ACCHS, the supply of oral health services fell very short of the demand and senior management identified that inadequate and inconsistent resources seriously undermined providing programs to treat disease and promote and sustain oral health care for Aboriginal people [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Policy making challenges including resource allocation and the governments` actions and interventions are considered as the fourth challenges of provision to oral health services (Table 3). Allocating adequate funding to the oral health needs of Indigenous Australians [27,28] was the strongest sub-theme. Including programs that aimed to reduce early childhood caries, increasing services to remote communities, developing the role of Aboriginal health workers, improving oral health literacy, establishing water uoridation and providing periodontal therapy are some effective interventions that can be compounded by the complex interplay between psychosocial and cultural determinants of both Indigenous Australians and oral health professionals.…”
Section: Geographic Barriers In Accessing Oral Health Servicesmentioning
confidence: 99%